EXPLORE THE FOUNDATIONS AND PRINCIPLES OF ISLAMIC FAMILY LAW - Sofiandi, Aldi; Irwansyah, Wawan; Wiranti, Wiranti; Irwan, Irwan; Maulina, Nia (ANAYASA : Journal of Legal Studies, 2024)
The aim of this research is to explore the foundations and principles of Islamic family law. The method used by the researcher is a qualitative research method with a library study type of research. This type of literature study research is used to explore an in-depth understanding of a topic or phenomenon by analyzing relevant literature and sources, which in this research is related to exploring the foundations and principles of Islamic family law. As for data, it is obtained through study and analysis of various references such as books, scientific journals, articles and other documents related to the topic being researched and then researchers draw common threads and conclude from the findings and research studies. The results of this research show that the literature study on exploring the foundations and principles of Islamic family law provides a comprehensive overview of the multifaceted nature of this legal framework. Rooted in the Quran and the Sunnah, Islamic family law encompasses principles related to marriage, divorce, child custody, inheritance, and broader ethical considerations. The literature reflects the ongoing efforts of researchers to analyze and interpret Islamic legal sources, shedding light on the adaptability of Islamic family law to different cultural and social contexts. As scholars continue to explore and debate various aspects of Islamic family law, the literature serves as a valuable resource for understanding the principles that govern family life within the Muslim community and their implications for individuals, families, and societies at large.